A Project pedagogy: a proposal that re-signifies learning at school - Mora, Claudia Patricia; Camacho, Damarys; Marulanda, Laura Cosntanza (Rastros Rostros, 2024)
In the 21st century, education needs to take a new direction that responds to the needs and experiences of children, who have been developing in an avant-garde world that offers them the possibility of developing, creating, imagining and enhancing all their knowledge, significant reading and writing skills and communicative competencies with ever-increasing demands.